Ressarcimento ao SUS: análise do repasse das operadoras de planos de saúde no período de 2001 a 2012 - Queiroz, Thiago Faustino de (2015)
The repayment to Unified Health System (Sistema Único de Saúde, SUS) is a legal obligation of the care of plans to reimburse the health care services provided in contracts, provided to its customers and their dependents, in public or private institutions, conveniadas or contractors, members of Single System health. The National Health Agency (Agência Nacional de Saúde Suplementar, ANS), the body responsible for the oversight of these operators and the collection of the reimbursement to SUS, has many difficulties to implement the effective reimbursement. This research aims to analyze the transfer of the health plan operators to the National Health System, and the use of health services financed by the SUS by beneficiaries of health plans and their costs generated to public funds for such uses as well to describe the main causes of low effectiveness of reimbursement to SUS. This is a statistical and quantitative study based on the financial figures of data relating to the 2001 to 2012 of ANS and secondary databases from the Ministry of Health (Ministério da Saúde) to system integration. A linear regression model was developed with SUS costs variables, by categories of beneficiaries with plans of health, and subjected to stress tests for validation. As a result it was concluded that, despite the achievements in the regulation of supplementary sector, ANS has a timid action regarding the reimbursement to SUS, as the R $ 5.38 billion charged of operators in the period 2001 to 2012, only R$ 350 million was effectively reimbursed. Such factors limiting the effective reimbursement are arranged in scope legal, institutional and operational.